1998
DOI: 10.1105/tpc.10.8.1233
|View full text |Cite
|
Sign up to set email alerts
|

Lotus corniculatus Nodulation Specificity Is Changed by the Presence of a Soybean Lectin Gene

Abstract: Plant lectins have been implicated as playing an important role in mediating recognition and specificity in the Rhizobium-legume nitrogen-fixing symbiosis. To test this hypothesis, we introduced the soybean lectin gene Le1 either behind its own promoter or behind the cauliflower mosaic virus 35S promoter into Lotus corniculatus, which is nodulated by R. loti. We found that nodulelike outgrowths developed on transgenic L. corniculatus plant roots in response to Bradyrhizobium japonicum, which nodulates soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 60 publications
0
28
0
4
Order By: Relevance
“…These lectins localize to root hair tips and are thought to help convey host-symbiont specificity by binding simultaneously to the plant cell wall and to saccharide moieties on the surfaces of compatible bacteria (41,43,79). A series of experiments in which a variety of transgenic plants expressed lectins from other species of legumes has shown that the presence of heterologous lectins often allows transgenic plants to respond to symbionts that are usually noncompatible, provided that the heterologous lectin can bind to the noncompatible bacteria and provided that the noncompatible bacteria make the proper Nod factor (42,79,171,172). For example, transgenic alfalfa that expressed pea lectin formed nodules and infection threads when inoculated with low numbers of R. leguminosarum bv.…”
Section: Adhesion Of Rhizobia To Root Hairsmentioning
confidence: 99%
“…These lectins localize to root hair tips and are thought to help convey host-symbiont specificity by binding simultaneously to the plant cell wall and to saccharide moieties on the surfaces of compatible bacteria (41,43,79). A series of experiments in which a variety of transgenic plants expressed lectins from other species of legumes has shown that the presence of heterologous lectins often allows transgenic plants to respond to symbionts that are usually noncompatible, provided that the heterologous lectin can bind to the noncompatible bacteria and provided that the noncompatible bacteria make the proper Nod factor (42,79,171,172). For example, transgenic alfalfa that expressed pea lectin formed nodules and infection threads when inoculated with low numbers of R. leguminosarum bv.…”
Section: Adhesion Of Rhizobia To Root Hairsmentioning
confidence: 99%
“…A gene encoding pea lectin conferred novel bacterial nodulation properties on clover plants; the transgenic clover plants were nodulated by the heterologous strain R. leguminosarum bv. viciae, which does not nodulate wild-type clover (110,411,503,505). Two Arabidopsis mutants have been described that are defective in their ability to bind A. tumefaciens (348,552).…”
Section: Binding To Host Surfacesmentioning
confidence: 99%
“…In addition, some plant lectins, such as soybean lectin (SBL), are released into the rhizosphere (52,55) and specifically stimulate rhizobial adsorption and infection (30,55). Although the mechanism of plant lectin action remains obscure, its role in restricting rhizobium-host specificity range was demonstrated in studies with transgenic plants (15,52).…”
mentioning
confidence: 99%